SYSTEMS AND METHODS FOR MANAGING NAVIGATION AMONG APPLICATIONS - LAI RUI; TIAN WEN-GUANG; XIAO XIN-YI (2015)
Systems and methods are provided for managing navigation among applications installed on an electronic device. According to certain aspects, an electronic device receives (1502) a selection of a graphical item displayed by a source application and an instruction to copy the graphical item. The electronic device stores (1514) an identification of the source application in a data record and navigates (1522) to a destination application. Further, the electronic device receives (1538) a command to paste the graphical item within the destination application and return to the source application, examines (1560) the data record to identify the source application, and automatically navigates (1570) to the source application.